Autonomic dysfunction in pulmonary arterial hypertension: Neurocardiological mechanisms and clinical implications - Ilma Nascimento; Victor Cavalcanti Medeiros; Ricely Almeida Tenório Rezende; Vitor Abreu Barreiro; Maria Júlia Torres Lira; Sergio Roberto Pereira da Silva Júnior; Caio Julio Cesar Santos Fernandes (Brain & Heart, 2026)
Pulmonary arterial hypertension (PAH) is a progressive cardiopulmonary disease characterized by pulmonary vascular remodeling, increased pulmonary vascular resistance, and right ventricular dysfunction. Although PAH is primarily defined by hemodynamic and vascular abnormalities, growing evidence suggests that autonomic nervous system dysregulation may contribute to its broader clinical phenotype. This narrative review examines the available evidence on autonomic dysfunction in PAH from a neurocardiological perspective, with emphasis on sympathetic and parasympathetic imbalance, cardiovascular reflexes, central autonomic regulation, neuropsychiatric manifestations, and potential clinical implications. Current evidence suggests that autonomic dysfunction may represent a relevant but still exploratory component of PAH pathophysiology. Heart rate variability and baroreflex sensitivity may provide complementary information beyond conventional hemodynamic assessment, but methodological heterogeneity and limited prospective data preclude routine clinical use. Similarly, autonomic-targeted interventions remain investigational. A more integrated brain–heart–lung framework may help clarify the relationship between pulmonary vascular disease, right ventricular adaptation, autonomic regulation, and patient-centered outcomes in PAH.